Características dos chief financial officer e escolhas contábeis: evidências da Alemanha, Brasil e Reino Unido - Almeida, Neirilaine Silva de (2018)
The factors that affect managers in accounting choices is one of the most prominent topics in accounting research. Numerous prior studies have examined contractual, economic and institutional factors which affect choice of accounting methods. This study differs from this approach by employing the Upper Echelons Theory and considering that organizational choices are affected by the observable characteristics of top management. Thus, the purpose of this paper is to examine associations between observable characteristics of Chief Financial Officer (CFO) and accounting choices. The dependent variable is an index that measures a manager's propensity to choose accounting policies that increase earnings and/or operating cash flow (OCF). The index consists of ten accounting policies collected from the financial statements of 175 entities located in Germany, Brazil and the United Kingdom (2010 – 2016). The results show that the observable characteristics of CFOs partially explain their accounting choices. Specifically, entities that tend to adopt accounting policies that increase earnings and/or OCF have CFOs that lack graduate education or greater internationalization. CFOs can use the flexibility inherent in accounting choices to adopt accounting policies that increase earnings and/or OCF in ways that fit their personal characteristics. Therefore, it may be beneficial to reflect on the potential benefits of reducing the use of certain accounting policies that affect financial statements These findings provide support for the thesis that, in addition to observing the contractual, economic and institutional factors, managers consider their personal characteristics when making accounting choices. Thus, the results of the study may contribute to future research on accounting choices by pointing out that the CFO’s observable characteristics also affect these choices.